PERKEMBANGAN KâEMANDIRIAN KEUANGAN DAERAH KABUPATEN/KOTA DI PROVINSI NUSA TENGGARA TIMUR PERIODE 2008 - 2012 - Putri, Adelia; Masdjojo, Gregorius N. (Proceeding Fakultas Ekonomi, 2014)
The regional autonomy which included fiscal decentrahzaflon requires having financial wdependence. Fiscal decentralization will give authonty to the local govcrinent to explore the potential of the area and obtain the transfer of the center in terms of fiscal balanceSource of funds used for the cousuuioa consists of Local Revenue, General Allocation Fund. Special Allocation Fund and Revenue Sharing. The obj of this research is South Lst Nusa Pnwuâice This study med to analyie the influence of Local Revenue prowrh General AIICICaIUW Famd pmwth Snecial Allocation Fund crnih and Reenue Sharing growth to Local Financial Independence Basal on calculation with panel data regression is found that Local Revenue growth has posiuve and significant impact on Local Financial Independence. General Allocation Fund growth has negative and ngnhlican( Impact on Local Financial Independence. Special Allocation Fund trowth has negative and significant impact on Local FinancLal Independence, Revenue Sharing growth has not significant impact on Local Fmancial Independence &ev words Local Revenue. General Aioconon Fw Special Allocation FumL lkvcniaâ Â£wanng. Local Frnwicii1 lndependesr.e